Evaluation of Effectiveness of Parcel Delivery Sector Companies in the Context of COVID-19 Pandemic - Žinytė, Ringailė; Jurkonienė, Gerda (Buhalterinės apskaitos teorija ir praktika, 2023)
The paper examines the impact of COVID-19 pandemic on operational effectiveness of parcel delivery sector companies operating in Lithuania. As demand of parcel delivery sector‘s services has increased, it is important to find out whether the impact of COVID-19 pandemic on operational effectiveness could be considered as positive even though the sector faces difficulties related to parcel delivery. The aim of the research is to evaluate the efficiency of parcel delivery sector companies operating in Lithuania during the COVID-19 pandemic. After the literature analyses, it was decided to examine the financial statements of 27 parcel delivery companies during the COVID-19 pandemic (2020-2021) and before the pandemic (2017-2019). During the investigation the impact of pandemic was analysed using the methods of correlation, regression, and logistics analysis. The main purpose of correlation analysis was to find connections between variables and by regression analysis to find causality between dependent and independent variables. The results of pandemic ware compared with results of pre-pandemic. After this, the results of pandemic have been applied in logistics analysis in forecasting process. Overall, it became clear that during the pandemic operational profit was more effective and costs were less effective comparing with results of pre-pandemic. In addition, the results of logistics analysis showed that there is a possibility that in the future operation profit will be ineffective and costs will be effective.